Handbook of international relations - Carlsnaes, Walter; Risse-Kappen, Thomas; Simmons, Beth A. (SAGE, 2002)
Drawing together a team of the world's leading scholars, this major new handbook provides a state-of-the-art review and guide to the study of international relations.
Keywords: International relations